Local environmental work 1995 - Bennulf, Martin (University of Gothenburg, 2015)
This survey forms part of the project ´Local environmental work - A study of local conditions and the interplay between economy and politics´. Other surveys used within this project are ´Opinion in Western Sweden 1995´, ´SOM-survey 1995´ and ´SOM-survey Western Sweden 1995´. In this survey heads of local environment departments had to give a description of environmental health work in their municipality. For a number of statements on local environmental work they had to state if they agreed or not. For eleven different environmental problems they had to point out what kind of funds and resources, i.e. money, technical expertise, planning resources, political interest and knowledge, civil interest and knowledge, that were lacking in the municipality. A number of questions dealt with environmental information, environmental policy and Agenda 21. The respondents had to state how much confidence they had in various institutions and groups in regard to their work for the environment, and how important they considered the same institutions and groups to be for the local environmental work. They also had to give their opinion on the importance of various environmental issues in their municipality, and how serious they considered different threats against the environment to be. Furthermore they had to give their opinion on a number of propositions given in the Swedish environmental debate and in the general political debate. Questions about leisure habits and values dealt with activities during the last year, health risks for the Swedish people, and importance of a number of values. Background information includes age, sex, education, occupation, size of household, and party preference.

Purpose:

As a part of a larger project in Local environmental work, this study aims to analyse governance, policies and goals related to local environmental policy-making.

Denna undersökning med tillhörande datainsamling ingår i projektet "Lokalt miljöarbete - En studie av lokala förutsättningar och samspelet mellan ekonomi och politik", tillsammans med bl. a. den nationella och den västsvenska SOM-undersökningen för år 1995. I denna studie ombeds Sveriges kommuners samtliga miljöchefer beskriva det lokala miljöarbete som bedrivs i kommunen. Detta genom en enkätundersökning under våren 1995. Enkäten innehåller dels påståenden som de svarande fick ta ställning till, och dels frågor om miljörelaterad problematik där man hade möjlighet att specificera vilka resurser som saknades i kommunen för att avhjälpa problemen. Vidare inkluderas frågor om förtroende, miljöpolitik och ekonomi. Bakgrundsvariabler som ålder och utbildning samt partipolitisk tillhörighet inkluderas också.

Syfte:

Lokalt miljöarbete 1995 är en del av projektet "Lokalt miljöarbete - En studie av lokala förutsättningar och samspelet mellan ekonomi och politik", vars huvudsyfte är att studera styrningsproblematiken på miljöområdet och att analysera i vilken grad miljöpolitikens målsättningar förverkligas på den lokala arenan.
Lokalt miljöarbete 1995
Keywords: General health and well-being; Allmän hälsa och välbefinnande; Information society; Informationssamhället; Environment and conservation; Miljö och naturvård; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap